Uji Aktivitas Antibakteri Pada Makanan Bekasam Ikan Bandeng Chanos chanos f Terhadap Bkteri Penyebab Penyakit Diare Escherichia coli - Jumriah Nur; Natasya Adibba Khanza (HEALTH SCIENCE & BIOMEDICAL JOURNAL, 2025)
Diarrhea is one of the leading causes of morbidity and mortality worldwide, particularly among children under the age of five. One of the primary pathogens responsible for diarrhea is Escherichia coli, which is often found due to poor food sanitation. Bekasam, a traditional Indonesian fermented fish product, is known to contain Lactic Acid Bacteria (LAB) that potentially have antibacterial effects. This study aims to isolate, identify, and test the antibacterial activity of LAB from fermented milkfish bekasam against Escherichia coli. The method used is descriptive experimental with a well diffusion approach. The observed parameter is the diameter of the inhibition zone of E. coli growth by LAB. The physicochemical test results showed that bekasam has a pH of 3.9. The identification of LAB showed Gram-positive bacillus morphology, non-motile, and catalase-negative. The antibacterial activity test results showed that LAB from milkfish bekasam has an average inhibition zone of 15 mm against Escherichia coli, categorized as strong antibacterial activity. This study concludes that milkfish bekasam has the potential as a natural antibacterial agent against E. coli and is likely to be developed as an alternative treatment or prevention of diarrhea based on traditional food.